Implementation of an Automated Attendance System with Integrated Face Recognition using Haar Cascade and LBPH Algorithm - Sharma, Shuchi; Sharma, Anirudh; Jain, Priyam; Popli, Ishant; Chahar, Harsh (International Journal of Computer Sciences and Engineering, 2023)
This research explores the implementation of a state-of-the-art attendance system utilizing face recognition technology with a focus on Haar Cascade and Local Binary Pattern Histogram (LBPH) algorithms. The primary objective of this system is to revolutionize traditional attendance management methodologies by incorporating computer vision techniques. The Haar Cascade algorithm is employed for precise face detection, ensuring accurate identification of facial features, while the LBPH algorithm enhances facial recognition robustness. The paper elucidates the architectural framework of the proposed system, delineates the algorithmic workflow, and presents empirical results demonstrating the efficacy of the implemented solution. By integrating these advanced algorithms, the developed attendance system not only automates the attendance tracking process but also provides a secure and efficient mechanism for organizations to manage attendance records in a contemporary and technologically sophisticated manner.